Modular, adaptive, and controlled : a practice-informed design framework for the responsible use of generative AI in continuing vocational education and training in the skilled trades - Neuwirth, Martin [Verfasser]; Taieb, Leonie [Verfasser]; Reinarz, Janin [Verfasser]; Kremzow-Tennie, Simeon [Verfasser]; Calderón-Merchán, Esteban [Verfasser]; Frohn-Schauf, Claudia [Verfasser]; Siebert, Kerstin [Verfasser]; Böttcher, Roland [Verfasser] (My University, 2026)
“Vocational continuing education and training (CVET) in Germany is increasingly shaped by digitisation, structural changes in the labour market and an acute shortage of skilled workers. These developments place increasing pressure on the skilled trades. Learning processes must therefore be flexible, workplace-oriented, and tailored to hetero geneous target groups that vary widely in experience and familiarity with digital education. This paper examines these challenges through the empirical lens of the ‘TraFuSMS – Training for Future Skills in Sustainable Mobility Solutions’ project. It addresses the following research questions: How can GenAI be used to support modular learning materials in heterogeneous target groups? What new roles and competencies are required of educational personnel when GenAI is embedded in content development? By answering and synthesising these questions, a pedagogical framework is developed that supports educators by using GenAI as an assistive tool in Vocational Education and Training (VET) systems.” (Excerpt, BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; S 1.5.2 Berufliche Weiterbildung; S 6.2 Fertigungsberufe; Medieneinsatz; 370; Künstliche Intelligenz; Berufliche Weiterbldung; Handwerksberuf; Medieneinsatz; Rahmenbedingungen